Overview of Physical and Psychological Health Conditions and Their Impact on the Quality of Life of Elderly People - Thorik Abdullah; Margaretha Sihobing (Generasi Sains Indonesia, 2026)
Population ageing has intensified concerns regarding the health and quality of life of elderly individuals living within community settings. This study aimed to examine the combined influence of physical and psychological health conditions on the quality of life of community-dwelling elderly populations. A quantitative cross-sectional design was employed involving elderly participants aged 60 years and above residing in urban and semi-urban communities. Data were collected through structured face-to-face interviews using validated instruments assessing chronic physical conditions, psychological health status, and multidimensional quality of life domains. The findings revealed a high prevalence of chronic illnesses, particularly hypertension and musculoskeletal disorders, alongside considerable levels of depressive and anxiety symptoms. Psychological health emerged as a stronger predictor of quality of life compared to most physical health variables. Furthermore, the interaction analysis demonstrated that psychological resilience may buffer the negative effects of chronic physical illness on elderly well-being. The novelty of this study lies in its integrative analysis of physical and psychological health within real-world community settings using a biopsychosocial perspective. The study highlights the importance of integrated community-based interventions addressing both physical and mental health to promote healthy ageing and improve elderly quality of life.